Phosphatidyl ethanolamine is essential for targeting the arginine transporter Can1p to the plasma membrane of yeast - Opekarová, Miroslava; Robl, Ingrid; Tanner, Widmar (Biochimica et biophysica acta, 2002)
In continuation of our previous study, we show that phosphatidyl ethanolamine (PE) depletion affects, in addition to amino acid transporters, activities of at least two other proton motive force (pmf)-driven transporters (Ura4p and Mal6p). For Can1p, we demonstrate that the lack of PE results in a failure of the permease targeting to plasma membrane. Despite the pleiotropic effect of PE depletion, a specific role of PE in secretion of a defined group of permeases can be distinguished. Pmf-driven transporters are more sensitive to the lack of PE than other plasma membrane proteins.
Keywords: transportní systémy pro bazické aminokyseliny; Saccharomyces cerevisiae Proteins; Schizosaccharomyces pombe Proteins; protonmotorická síla; proteiny přenášející monosacharidy; Proton-Translocating ATPases; Saccharomyces cerevisiae; Mannosyltransferases; fosfatidylethanolaminy; membránové proteiny; Membrane Proteins; Fungal Proteins; transportní systémy aminokyselin; Arginine; Vesicular Transport Proteins; proteiny usnadňující transport glukosy; Cell Membrane; mannosyltransferasy; Amino Acid Transport Systems; Proton-Motive Force; Phosphatidylethanolamines; vezikulární transportní proteiny; buněčná membrána; Saccharomyces cerevisiae - proteiny; Schizosaccharomyces pombe - proteiny; arginin; Amino Acid Transport Systems, Basic; protonové ATPasy; Glucose Transport Proteins, Facilitative; fungální proteiny; Monosaccharide Transport Proteins